Selective Adsorption of CH4/N2 on Ni-based MOF/SBA-15 Composite Materials - Hong Liu; Wei Ding; Shaohua Lei; Xupei Tian; Fubao Zhou (Nanomaterials, 2019)
Spherical SBA-15-based metal⁻organic framework (MOF) composite materials were prepared, with nickel as the metal center of MOFs. The materials were characterized via scanning electron microscopy, X-ray fluorescence analysis, X-ray powder diffraction, Fourier-transform infrared spectroscopy, and nitrogen (N2) adsorption⁻desorption. The methane (CH4) or N2 high-pressure adsorption isotherms of the samples were measured and compared. The specific surface area and adsorption capacity of the composite materials were generally higher than the pristine MOFs, but were much lower than the synthesized SBA-15. The selectivity of the samples toward a binary gas mixture was determined from the Langmuir adsorption equation. The results revealed that, of all the samples, the MOF-2/SBA-15 sample had the best CH4/N2 adsorption selectivity, with an adsorption selection parameter (S) of 11.1. However, the adsorption of MOF-2/SBA-15 was less than that of spherical SBA-15, due to partial plugging of the pores during the synthesis process. Further research is essential for improving the performance of spherical SBA-15-based MOF materials and (in turn) the enrichment of CH4 from the CH4/N2 mixture.